Intermolecular H···O═C bonds induced 2D self‐assembly of thiophene based diketopyrrolopyrrole derivative. (14th February 2017) - Wu, Yican; Li, Jinxing; Zha, Bao; Miao, Xinrui; Ying, Lei; Deng, Wenli
Abstract : Compounds with diketopyrrolopyrrole (DPP) and thiophene moieties have attracted considerable attention because of their promising charge transport properties. The molecular conformation and self‐assembly of 2, 5‐dihexadecyl‐3, 6‐di(thiophen‐2‐yl)‐2, 5‐dihydropyrrolo[3, 4‐c]pyrrole‐1, 4‐dione (TDPP‐C16) molecule have been investigated by scanning tunneling microscopy and density functional theory alculation. The TDPP‐C16 molecules adsorb with their optimized S‐shaped conformation and form a zipper‐like pattern on highly oriented pyrolytic graphite surface. R and S rotated structures are observed. The nanostructure is dominated by intermolecular double hydrogen bonds between C═O of the DPP units and hydrogen atom of thiophene rings in the neighboring molecules in each row. Atomic force microscopy and density functional theory calculation also display the existence of strong intermolecular hydrogen bonding. The results provide molecular evidence for the intermolecular interactions of the surface structure, which could benefit to the design of the organic semiconducting materials and understanding of underlying principle of charge transfer process. Copyright © 2017 John Wiley & Sons, Ltd.